2020
DOI: 10.1371/journal.pone.0238906
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship quality and mental health during COVID-19 lockdown

Abstract: Catastrophes are known to have an impact on relationships as well as on mental health. This study evaluated differences in several mental health and well-being measures according to relationship quality during the Coronavirus Disease (COVID-19) pandemic and related lockdown measures. A cross-sectional online survey was launched four weeks after lockdown measures were implemented in Austria. Relationship quality was measured with the Quality of Marriage Index (QMI), and mental health measures included quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
152
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(200 citation statements)
references
References 23 publications
15
152
0
10
Order By: Relevance
“…For example, anxiety is the biggest mental challenge people face today, followed by their inability to work remotely and feelings isolation from their social life. It is also has become imperative to pay attention to other lifestyle factors that can enhance mental wellbeing such as sleep quality, dietary behaviors, physical activity, sitting time and sedentary life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, anxiety is the biggest mental challenge people face today, followed by their inability to work remotely and feelings isolation from their social life. It is also has become imperative to pay attention to other lifestyle factors that can enhance mental wellbeing such as sleep quality, dietary behaviors, physical activity, sitting time and sedentary life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These were imposed by several governments and were reported to be “very effective” for people who choose to stay indoors [ 8 ]. However, home confinement, and curfews are a cause of concern as they have impacted physical activity (PA), eating behaviors, and mental health of the people globally [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One recent review reported negative psychological effects and longer quarantine time was a stressor ( Brooks et al, 2020 ). There are a growing number of studies about the impact of social quarantine on anxiety on the general population of different countries ( Campos JADB et al,2020 ; Pieh C et al, 2020 ; Rossi R et al,2020 ). A recent meta-analysis showed compelling evidence for adverse mental health effects of isolation and quarantine, in particular depression, anxiety, stress-related disorders ( Jonathan H et al,2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of sample size and power were performed while using Sample Size Calculator Qualtrics (https://www.qualtrics.com/blog/calculating-sample-size/), as previously reported in other studies (31,32).…”
Section: Sample Size Calculationmentioning
confidence: 99%